Pengaruh Kinerja Lingkungan dan Biaya Lingkungan terhadap Nilai Perusahaan dengan Kepemilikan Manajerial sebagai Variabel Moderasi - Salam, Syaila; Afriyenti, Mayar (Universitas Negeri Padang, 2025)
This research aims to determine the effect of environmental performance and environmental cost on firm value with managerial ownership as a moderating variable. Firm value is the dependent variable, while environmental performance and environmental cost are independent variables. The moderating variable is managerial ownership. Firm value is measured by the Tobin’s Q ratio. Environmental performance is measured by the PROPER rating. Environmental cost is measured by dividing environmental cost by net profit after tax. Managerial ownership is measured by dividing management shares by total shares. The data consists of annual and sustainability reports of mining companies in Indonesia listed on the Indonesia Stock Exchange for 2019-2023. Purposive sampling and moderated linear regression were used for data analysis. The results showed that environmental performance had a positive effect on firm value, while environmental cost had no effect on firm value. Managerial ownership was unable to moderate the relationship between environmental performance and environmental cost on firm value.